1987
DOI: 10.1093/nar/15.23.10066
|View full text |Cite
|
Sign up to set email alerts
|

Vectors for cell-free expression and mutagenesis of protein-coding sequences

Abstract: We have developed a vector (pTL-8) to facilitate cell-free expression of cloned protein-coding sequences (1). The 5' non-coding and initial coding sequences of the tobacco etch virus (TEV) RNA genome were inserted downstream from an SP6 promoter, allowing foreign coding sequences to utilize the translational initiation properties of the TEV leader for cell-free translation from synthetic transcripts. Efficient and accurate initiation of translation occurs without the need for 5 capping procedures (1). A family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…This is the predicted size of precursor which has not been proteolytically processed. Similar mutation and expression studies have been reported for the TEV N I a proteinase (Carrington & Dougherty, 1987) and are presented in Fig. 4 (b).…”
Section: Sks~-kg~bdvnois--ic-l-nssd~h---mfg-gfg--iitn-hlfrrnng-~tv-s-supporting
confidence: 85%
See 2 more Smart Citations
“…This is the predicted size of precursor which has not been proteolytically processed. Similar mutation and expression studies have been reported for the TEV N I a proteinase (Carrington & Dougherty, 1987) and are presented in Fig. 4 (b).…”
Section: Sks~-kg~bdvnois--ic-l-nssd~h---mfg-gfg--iitn-hlfrrnng-~tv-s-supporting
confidence: 85%
“…A portion of pSMV-34 was subcloned into the transcription vector pTL-37 (Carrington et al, 1987). This plasmid, referred to as pTL-TSP, was generated by digesting pSMV-34 with NeoI, filling in using Klenow fragment, digesting with XbaI and ligating into pTL-37 which had been digested with Sinai and Xbal.…”
Section: Cell-free Transcription and Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard recombinant DNA techniques (Sambrook et al, 1989) were used to insert the PCR-generated products described above into the transcription vector pTL27N. This plasmid vector was similar to pTL17 described previously (Carrington et al, 1987), except that an origin of replication for single-stranded DNA production was inserted and a site-directed mutation creating an NcoI restriction site at the ATG translation start codon (TEV nucleotides 143 to 145) was introduced (Taylor et al, 1985a, b).…”
Section: Methodsmentioning
confidence: 99%
“…1 (b) and are referred to as pTL-50/71, pTL-58/30 and pTL-combo. All three plasmids positioned the coding sequences downstream of a TEV 5' leader cassette to promote efficient translation in rabbit reticulocyte lysates (Carrington et al, 1987).…”
Section: Methodsmentioning
confidence: 99%